The Association of CD4, CD8, and CD4/CD8 Ratio with Thyroid Dysfunction in HIV/AIDS - Sri Mulyani; MI. Diah Pramudianti; Dian Ariningrum (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Incidence of thyroid dysfunction increases in HIV/AIDS patients. It can be a hypothyroid or hyperthyroid, with subclinical hypothyroid predomination. Thyroid dysfunction is associated with the progression of HIV and low CD4 counts. There has been controversy over how HIV affects thyroid function. Opportunistic infections and HBV/HCV co-infections might increase the probability of thyroid dysfunction. Medication of HIV is also an important factor of thyroid dysfunction. Research shows that the use of ART increases the probability of thyroid dysfunction. This study aimed to analyze the association between CD4 counts, CD8, CD4/CD8 ratio, and HIV RNA viral load with thyroid dysfunction in HIV/AIDS patients. An observational study with a cross-sectional design was conducted from August to September 2020 in Dr. Moewardi Hospital, Surakarta on 60 HIV/AIDS patients. All subjects were 18-60 years old. The research data were analyzed with a 2x2 test table to determine the Prevalence Ratio (PR) of each variable, then multivariate analysis with logistic regression was continued. The study showed 6.7% thyroid dysfunction in HIV/AIDS patients, 5% subclinical hyperthyroidism, and 1.7% subclinical hypothyroidism. The CD4 counts [PR 13.36 (95% CI: 1.53-116,65; p=0.017) and CD8 counts [PR 0.91 (95% CI: 3 0.02-0.51; p=0.032)] significantly associated with thyroid dysfunction in HIV/AIDS patients. CD4 counts < 200 cells/mm and 3 CD8 counts ≥500 cells/mm were associated with the incidence of thyroid dysfunction in HIV/AIDS patients, while CD4/CD8 ratio and HIV RNA viral load were not associated. CD4 count was not an independent predictor of thyroid dysfunction in HIV/AIDS patients.